T-violating effect in $ν_τ (\bar{ν}_τ)-$nucleon quasielastic scattering - Fatima, Atika; Athar, Mohammad Sajjad; Singh, Sukhbinder (SciPost physics proceedings, 2025)
The production cross sections and polarization observables of the τ τ leptons produced in the |Δ S| = 0 | Δ S | = 0 and 1 1 induced ν_{τ}(\bar{ν}_{τ})-N ν τ ( ν ‾ τ ) − N quasielastic scattering have been studied. The effect of T violation, in the case of Δ S=0 Δ S = 0 and 1 processes, and the SU(3) symmetry breaking effects, in the case of Δ S=1 Δ S = 1 processes, on the total scattering cross sections as well polarization observables are explored. Experimentally, it would be possible to observe these effects in the forthcoming (anti)neutrino experiments like DUNE, SHiP and DsTau.